Effect of NPK Fertilizer and Humic Acid Dosage on the Growth and Yield of Paddy Rice Plants (Oryza sativa L.) - Linlin Parlinah; Noertjahyani Noertjahyani; Elly Roosma Ria; Nunung Sondari; Tien Turmuktini; Lia Amalia; Tri Mutiara Dewi (Media Pertanian, 2026)
Repeated processing of rice fields affects soil quality and degradation, which in turn impacts rice production. Therefore, a combination of NPK and humic acid is needed to prevent a decrease in NPK and to improve soil structure. this article studies about the effect of NPK fertilizer dosage and humic acid on the growth and yield of paddy rice. The experimental design used was a Split Plots Design with NPK as the main plot and Humic Acid as the subplot with each treatment having 4 dose levels and each repeated twice. Main plot of NPK dosage consists of 0 kg ha-1, 100 kg ha-1, 200 kg ha-1, and 300 kg ha-1. The subplots of humic acid doses consist of 0 g ha-1, 1500 g ha-1, 3000 g ha-1, and 4500 g ha-1. The results showed that there was an interaction between the dose of NPK fertilizer and humic acid on plant height, number of tillers, root drop ratio, number of productive tiller, number of grains per panicle, percentage of filled grain, weight of harvested dry grain per hill, weight of dry grain harvest per plot, weight of milled dry grain per hill and weight of milled dry grain per plot, except for the weight of 1000 grains. The dose of NPK fertilizer as much as 206.30 kg ha-1and the dose of humic acid as much as 2.928 kg ha-1 gave optimum results on the weight of dry milled grain which produced 6.15 kg per plot or equivalent to 10.250 tons ha-1.